2016
DOI: 10.1371/journal.pone.0158905
|View full text |Cite
|
Sign up to set email alerts
|

A Single Nucleotide Polymorphism in the Il17ra Promoter Is Associated with Functional Severity of Ankylosing Spondylitis

Abstract: The aim of this study was to identify new genetic variants associated with the severity of ankylosing spondylitis (AS). We sequenced the exome of eight patients diagnosed with AS, selected on the basis of the severity of their clinical parameters. We identified 27 variants in exons and regulatory regions. The contribution of candidate variants found to AS severity was validated by genotyping two Spanish cohorts consisting of 180 cases/300 controls and 419 cases/656 controls. Relationships of SNPs and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…A weak association between rheumatoid arthritis and the promoter IL17A rs2275913 was found in the Norwegian population and more recently in the Brazilian population [ 7 , 32 ]. Specifically, with the risk of AS and its severity, a strong association was observed with the rs4819554 SNP in the promoter region of IL17RA in two Spanish cohorts of patients and controls, but not involving the IL17A and IL17F polymorphisms that we have studied here [ 33 ]. Therefore, in patients of Northern Italy, IL17A and IL17RA gene allelic variants were not associated with PsA susceptibility [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A weak association between rheumatoid arthritis and the promoter IL17A rs2275913 was found in the Norwegian population and more recently in the Brazilian population [ 7 , 32 ]. Specifically, with the risk of AS and its severity, a strong association was observed with the rs4819554 SNP in the promoter region of IL17RA in two Spanish cohorts of patients and controls, but not involving the IL17A and IL17F polymorphisms that we have studied here [ 33 ]. Therefore, in patients of Northern Italy, IL17A and IL17RA gene allelic variants were not associated with PsA susceptibility [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor (TNF), interleukin- (IL-) 1, IL-6, and IL-23/IL-17 are major inflammatory cytokine pathways of great interest from serial studies of single nucleotide polymorphisms, cytokine receptors, and associated intracellular signaling molecules. Among these inflammatory cytokines, IL-17 plays a dominant role in the inflammatory and proliferative cascades of human SpA [ 4 , 5 ]. In this review, we have discussed the contributing role of the IL-17 pathways in the pathophysiology of SpA from current evidence of genetic associations, studies in animal models, and expression of IL-17 in human SpA.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated a lack of association between IL17A SNP, rheumatoid arthritis and secondary Sjögren's syndrome (Carvalho et al., ) in a study with 206 individuals, but a weak association was demonstrated in a larger sample (Nordang et al., ). In ankylosing spondylitis, a SNP in the promoter region of IL17RA was associated with an elevated risk, with a stronger association in individuals with severe forms (Vidal‐Castiñeira et al., ). Inflammatory bowel diseases seem to be influenced by IL17 SNPs, and there seems to be an interaction between the risk haplotypes in IL23R and IL17A in individuals with ulcerative colitis (Yu et al., ).…”
Section: Discussionmentioning
confidence: 99%